Intrauterine death of one twin - Reyna-Villasmil, Eduardo (2018)
Multiple pregnancies, most of which are twins, have a substantially increased risk of fetal morbidity and mortality compared to single pregnancies. The fetal death of one of the twins in monochorionic twin pregnancies is more frequent than in twin dichorionic pregnancies. Intrauterine fetal death occurs in 1-7% of all twin pregnancies and greatly increases the rate of complications of the surviving twin including fetal loss, preterm birth, and end organ damage. The gestational age at which intrauterine fetal death occurs and the chorionicity of the multiple pregnancy are the two most important factors when considering the risks of the surviving twin. The morbidity and mortality of these pregnancies may decrease with risk identification and intensive prenatal surveillance. Monochorionic pregnancies are more difficult to manage, and often pregnancies are interrupted at 34-36 weeks. Dichorionic pregnancies can be interrupted closer to term.